Views and Attitude of Religious Leaders towards the Ideology of Pancasila: The Perspectives of Five Religions in Indonesia - *, Winarno; *, Muchtarom; Yuliandari, Erna; Ediyono, Suryo (IJRDO - Journal of Social Science and Humanities Research, 2016)
Pancasila is the ideology of Indonesian nation. As an ideology, it functions as a collective ideal and instrument for unity. Its functions are influenced by responses and acceptance from all citizens including certain groups existing in the society. This research aims at finding out the religious leaders’ responses towards Pancasila. It employs qualitative descriptive method. The data were collected through interview with some informants who were selected using purposive sampling method, observation, and document analysis. The informants include figures and boards of religious social organizations. Meanwhile, the validity was analyzed using resource and method triangulations, and the data were analyzed using interactive analysis technique. The research findings indicate that responses of religious believers to the ideology of Pancasila are manifested by comprehending it along with theological interpretation and by accepting its values according to certain religious belief. The religious believers accept Pancasila as the philosophical foundation because it has been a political agreement and it functions to integrate the heterogeneous population of Indonesia.